Small for gestational age (SGA) neonates show reduced suppressive activity of their regulatory T cells - Steinborn-Kröhl, Andrea; Engst, Martina; Hänsch, Gertrud Maria; Mahnke, Karsten; Schmitt, Edgar; Meuer, Stefan; Sohn, Christof (Clinical immunology, 2010)
Little information exists concerning the role of fetal regulatory T cells (Tregs) during intrauterine development. We examined whether complications such as reduced birth weight or the occurrence of preterm labor were associated with deficiencies in the number or in the immunosuppressive activity of Tregs in the fetal circulation. Their total number did not change during normal or complicated pregnancy. In contrast, their level of FoxP3 expression decreased continuously with gestational age and was significantly reduced in the presence of spontaneous term, but not preterm labor. In small for gestational age (SGA) neonates, FoxP3 expression was constantly decreased when compared to age matched healthy neonates. In accordance with the low FoxP3 expression, the suppressive activity of the Tregs from spontaneously term delivered and from SGA babies was significantly reduced. We propose that the level of FoxP3 expression in the fetal Tregs may be a potential regulator of their suppressive activity.
Gesehen am 08.11.2023